A study of cytological pattern of cervical papanicolaou smears in western Rajasthan, India - Rawat, Kiran; Rawat, Narendra; Mathur, Navgeet; Mathur, Medha; Chauhan, Nitesh; Tinna, Rajat; Kakkar, Rahul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is one of the most common cancers of Indian females. Western Rajasthan differs a lot from rest of India in respect of geographical conditions, environment, culture, population density etc. and it also has relatively lower literacy rate which is one of the risk factor for many diseases. The objective of this study was to estimate the prevalence of cervical cytological pattern in females of western Rajasthan by using conventional Papanicolaou (Pap) smears for the screening of inflammatory, premalignant and malignant lesions of the cervix. Methods: This cross sectional study was conducted at tertiary care institute of western Rajasthan for 1.5 year duration, on 1768 females who were screened by Pap smear examination. After staining with conventional Papanicolaou technique, all smears were classified as per Bethesda nomenclature. Results: Out of 1768 smears 1039 (58.7%) were abnormal Pap smears, 445 (25.1%) were normal Pap smears while 284 (16.1%) smears had inadequate sample material to be examined. Out of 1039 abnormal smears, 956 (92.01%) smears reported to have inflammatory/reactive changes whereas 26 (2.50%) had atrophic changes in Pap smear and abnormality in epithelial cell was reported in 57(5.49%) smears. Conclusions: Pap smear examination is an effective screening procedure to detect cervical cytological abnormalities. Routine cytological screening by Pap smear should be offered to all women above 19 years or within 3 years of sexual activity. It is recommended to improve the awareness about the disease amongst females and skills of health care personal about proper preparation of Pap smear.